A study of students’ performance in Kenya Certificate of Secondary Education with special reference to Biology - Ngesu, Lewis Muli; Kaluku, Esther Nthoki (IJRDO- Journal of Educational Research, 2017)
Many secondary schools in Kenya have been performing poorly in Kenya Certificate of Secondary Education (KSCE) in Biology examination over years. Often the teacher is blamed for poor performance among other factors. The purpose of this study was to investigate students performance in Biology in KCSE in secondary schools in Central division of Machakos district. The study was conducted in twelve secondary schools in the division in the categories of national, county and district. Data was collected from Form four Biology students, Biology teachers, Heads of Science department and heads of secondary schools in the division through the use of a questionnaire and interviews. The design of the study was descriptive survey and stratified sampling was used to select participants depending on the category of the school. The study revealed that syllabus coverage and effective practical sessions were the major predictors of good performance in Biology. The study concludes that student’s performance in Biology at KCSE level seems to be influenced by a combination of factors (Teaching methodologies, teacher’s related factors, school related and social-economic factors). The Kenyan government should intensify its efforts to train and retrain Biology teachers through conducting induction courses, seminars and refresher courses on teachers of Biology.